2016
DOI: 10.1016/j.coph.2016.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Vesicle-MaNiA: extracellular vesicles in liquid biopsy and cancer

Abstract: Normal and tumor cells shed vesicles to the environment. Within the large family of extracellular vesicles, exosomes and microvesicles have attracted much attention in the recent years. Their interest ranges from mediators of cancer progression, inflammation, immune regulation and metastatic niche regulation, to non-invasive biomarkers of disease. In this respect, the procedures to purify and analyze extracellular vesicles have quickly evolved and represent a source of variability for data integration in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 83 publications
(85 reference statements)
1
42
0
2
Order By: Relevance
“…EVs are produced by normal and cancerous cells and harbour molecular features of their cells of origin [27]. This encapsulated material can exert biological and metabolic functions [4,14,15,28], which makes them entities of tremendous interest in cancer biology, both at the level of biomarker discovery and mechanistic.…”
Section: Discussionmentioning
confidence: 99%
“…EVs are produced by normal and cancerous cells and harbour molecular features of their cells of origin [27]. This encapsulated material can exert biological and metabolic functions [4,14,15,28], which makes them entities of tremendous interest in cancer biology, both at the level of biomarker discovery and mechanistic.…”
Section: Discussionmentioning
confidence: 99%
“…Intercellular transfer of proteins in communication between cells play an important role in physiological processes . EVs have been reported to transfer tumor‐derived proteins in their membranes or lumens . It has been reported that membrane‐derived EVs carried the oncogenic receptor EGFRvIII participated in the processes of aggressive human brain tumors .…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, cancer‐derived exosomes have inherent potential to be chemoresistance biomarkers because of their ubiquitous presence in biofluids . The characterization of cancer‐derived exosomes, particularly their molecular cargo, is being developed as a strategy to monitor cancer therapy and predict tumor progression and metastasis . Based on the previous research, Eleni et al clarified their point that using exosomes as biomarkers could contribute to new methodologies in non‐invasive diagnosis, anticancer therapy, and prognosis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Torrano et al [17] provide an updated view of the potential of exosomes and microvesicles as cancer biomarkers and the available technologies for their isolation. Despite predicting an exciting bright future for EVs and their applicability in liquid biopsy, they recognize that there is still a long way and many challenges to solve for their clinical use as biomarkers of disease.…”
Section: Liquid Biopsy Through Tumor-educated Platelets (Teps)mentioning
confidence: 99%